Maillard Reaction Products Inhibit Oxidation of Human Low-Density Lipoproteins in Vitro - Dittrich, Ralf; El-Massry, Khaled Farouk; Kunz, Katrin; Rinaldi, Francesco; Peich, Carlo; Beckmann, Matthias; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2003)
Dietary intake of antioxidants has been associated with a reduced risk of cardiovascular diseases, which is very likely caused by their capability of prevent oxidation of low-density lipoproteins (LDL). During food processing and storage, substances with antioxidative properties are formed by Maillard reactions. In this study, the activity of Maillard products to inhibit copper-induced oxidation of human LDL in vitro was investigated. D-Glucose was heated with an equimolar amount of glycine, L-lysine, or L-arginine, for 1 h under reflux. The increase of the antioxidative activity (AOA) of the Maillard mixtures was highly significant compared to the control mixtures. Additionally, two defined Maillard products with amino reductone structure were tested. 3-Hydroxy-4-(morpholino)-3-buten-2-one (1) and amino hexose reductone (2) showed a significant and dose dependent AOA. Compound 1 was about half as active as ascorbic acid, which served as positive control. Thus, it can be concluded that Maillard products, particularly those with amino reductone structure, have the strong potential to inhibit LDL oxidation.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.llmch.mailla_0
Keywords: Amino hexose reductone; Amino reductones; LDL oxidation; Low-density lipoprotein; Maillard reaction